(untitled) (Bangladesh Journal of Medicine, 2026)
Background: Worldwide, 350 million people are chronically infected with HBV, and >50% of HCCs are attributable to HBV infection. Among them, a significant portion presents with a space-occupying lesion (SOL) in the liver and is detected incidentally. Alpha-fetoprotein (AFP) has long been considered the ideal serological marker for detecting hepatocellular carcinoma (HCC). However, limited studies were conducted to reveal the correlation between serum alpha-fetoprotein level & FNAC findings of liver SOL in patients with chronic HBV infection. Therefore, this study aimed to assess the relation between serum alpha-fetoprotein level & ultrasound-guided FNAC findings of liver SOL in patients with chronic HBV infection. Methods: The study was a cross-sectional observational study conducted at the Department of Hepatology & Medicine in Dhaka Medical College Hospital. The study duration was six months. Formal ethical approval was taken before the commencement of the study. Adult patients of chronic HBV infection with newly diagnosed liver SOL through USG admitted to the DMCH were approached and selected according to the selection criteria. Following the description of the study’s purpose, methods, benefits, and hazards, informed written consent was taken from each subject. All patients were subjected to a detailed history, clinical examination, and relevant investigations. Data were collected using qualitative and quantitative methods, using a questionnaire designed for the researcher’s study. After collection, the data were edited manually and prepared for data entry. The final analysis was done by using SPSS 23. Results: Out of 70 SOL in the liver with chronic HBV patients, the mean age was 49.11±12.78 SD (years) [age range 25-72 years] with 80% male and 20% female representation. The majority of the patients (48.6%) had AFP levels were 1 – 10 ng/ml, and 39% had above 400 ng/ml, followed by 7.1% between 11 – 100 ng/ml and 5.7% between 101 – 400 ng/ml. The mean serum AFP level was 5611.94±14861.24 SD (ng/ml). FNAC showed that 42% had well-differentiated carcinoma, 20% had moderately differentiated carcinoma, and 38% had poorly differentiated carcinoma. Rising of alpha-fetoprotein is significantly correlated with cytopathologic grading (p<.05). Conclusion: Serum alpha-fetoprotein level is significantly correlated with the findings of histological grading of liver SOL in patients with chronic HBV infection. Bangladesh J Medicine 2026; 37(2): 121-127